Régulation et institutions en économie du sport - Wladimir Andreff (Revue de la Régulation)
Regulation and institutional choice in sports economics. Different institutional options are compared between North American (closed league) and European  (open league) professional sports. Significant (‘quasi-socialist’) regulation in American leagues contrasts with increasing deregulation in European professional sports. In Europe, skyrocketing TV broadcasting rights are concentrating financial resources on a few rich clubs. This undermines the competitive balance of domestic championships, and calls for more regulation.